The changes in FIGO staging for carcinoma of the cervix uteri - Sehnal, B; Sláma, J; Kmoníčková, E; Dubová, O; Zikán, M (Ceska gynekologie, 2019)
INTRODUCTION: The carcinoma of the cervix uteri is the fourth most common cancer in women worldwide and more than 85% of these cases occur in developing countries. Altogether 822 new cases were found in the Czech Republic during 2016 which means the incidence 15,3 new diseases/100,000 women. OBJECTIVE: To provide an overview of changes in FIGO (International Federation of Gynecology and Obstetrics) staging for carcinoma of the cervix uteri with an incorporation of possible imaging methods and/or pathological findings, and clinical assessment of tumor size and extent. SETTINGS: Gynecologic Oncology Center, Department of Gynecology and Obstetrics, Hospital Na Bulovce and 1st Medical School of Charles University, Prague; Gynecologic Oncology Center, Department of Gynecology and Obstetrics, General Faculty Hospital and 1st Medical School of Charles University, Prague; Institute of Radiation Oncology, Hospital Na Bulovce, Prague. METHODS: For this review, we have used the results of studies, review articles, and guidelines of oncogynecologic organisations on the cervical cancer published in English. They were identified through a search of literature using PubMed, MEDLINE-Ovid, Scopus and Cochrane Library with the keywords. We summarize the new classification, main changes compared to the former one and their clinical impact. CONCLUSION: Lateral extension measurement is removed in the stage IA, the only criterion is the measured deepest invasion.
Keywords: Carcinoma; Cervix Uteri; Gynecology; Humans; cervix uteri; Female; nádory děložního čípku; lidé; ESGO; Lymphatic Metastasis; lymfatické metastázy; karcinom; staging nádorů; ženské pohlaví; staging; carcinoma; Czech Republic; Uterine Cervical Neoplasms; FIGO; Neoplasm Staging; gynekologie; Česká republika